Global perspectives on cancer survivorship: From lost in transition to leading into the future - Truant, Tracy L. (Can Oncol Nurs J, 2017)
In the decade since the Institute of Medicine’s 2006 landmark report, entitled From cancer patient to cancer survivor: Lost in transition, cancer survivorship increasingly has become a distinct phase in the cancer journey. While much progress has been made toward creating a system of care that optimally addresses survivors’ needs, significant gaps remain. An international symposium to discuss and explore global challenges in cancer survivorship care was held at the Canadian Association of Nurses in Oncology (CANO/ACIO) conference in Calgary, Alberta, in October 2016. In this paper, we summarize presentations from that symposium, exploring cancer survivorship care from Canadian, American, and International perspectives, and describing challenges, issues and gaps. Strategies are also discussed for oncology nurses, individually and collectively, to provide future leadership in shaping survivorship care to be more person centered and equity oriented.